Pour l'avenir de la France par l'union des forces ouvrières et dèmocratiques. Jacques Duclos (Parti Communiste Français, 1969)
Black and white portrait of Jacques Duclos Suggested translation: For the future of France through the union of working and democratic forces PO-1878